2013
DOI: 10.2134/jeq2012.0098
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Leaching during Establishment of Simulated Residential Landscapes

Abstract: Research evaluating nutrient losses during the establishment of plant material in mixed residential landscapes is limited. The objectives of this study were to determine the effect of vegetative cover type, compost application, and tillage on nutrient losses during the establishment of landscape plants. Twenty-four small plots constructed with subsoil fill were planted with St. Augustinegrass [ (Walter) Kuntze] and mixed ornamental species in a randomized complete block design. Plots received composted dairy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…This indicates that in summer time most input water fulfils plant water needs through evapotranspiration while in winter as a consequence of the dormancy in most plant species, the evapotranspiration rate decreases significantly which results in an increased leachate fraction in winter. These findings confirm a wellknown hypothesis and is consistent with the finding of Loper et al (2013) who stated that under both vegetation types of woody plants and turf grasses, a large portion of input water (either irrigation or rainfall) was retained as soil moisture or subject to ET rather than drainage loss. …”
Section: Drainage Water Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that in summer time most input water fulfils plant water needs through evapotranspiration while in winter as a consequence of the dormancy in most plant species, the evapotranspiration rate decreases significantly which results in an increased leachate fraction in winter. These findings confirm a wellknown hypothesis and is consistent with the finding of Loper et al (2013) who stated that under both vegetation types of woody plants and turf grasses, a large portion of input water (either irrigation or rainfall) was retained as soil moisture or subject to ET rather than drainage loss. …”
Section: Drainage Water Qualitysupporting
confidence: 92%
“…Woods et al (2013) reported a significant change in deep drainage and salt transport in response to changes in soil water balance conditions while at larger scales the changes were more influenced by surface topography. This finding is consistent with the outcomes of Loper et al (2013) who investigated the effect of vegetation cover types on leaching from early established landscape plots. They reported that different leachate volumes and nutrient leaching were primarily because of differences in root density and shoot biomass resulting in different rates of water availability to the plants.…”
Section: Drainage Water Qualitysupporting
confidence: 90%
“…Likewise Loper et al [17] did not observe significant increases in nitrate leaching after additions of composted dairy manure (~0.5 cm thick) to turf; however, the compost increased nitrate leaching under ornamentals. In addition to compost, native prairie grasses [18] and forbs [11] have greater rooting depth than normal lawn mixtures.…”
mentioning
confidence: 84%
“…However, recent studies comparing nutrient leaching from landscapes containing mixed woody ornamental species and turfgrass questioned the function of ornamental plants in urban landscapes (Cisar et al, 2004; Erickson et al, 2001; Loper et al, 2013). These studies indicated that newly planted mixed ornamental landscape plots leached greater inorganic N (NO 3 –N and NH 4 –N) (Erickson et al, 2001), P (Loper et al, 2013), and K (Erickson et al, 2005) than turfgrass monoculture. However, none of these studies (Cisar et al, 2004; Erickson et al, 2001; Loper et al, 2013) extended past the plant establishment phase to compare vegetation effects on nutrient leaching from mature landscapes.…”
mentioning
confidence: 99%